Gonadal development in a landlocked population of pejerrey fish Odontesthes argentinensis during spawning season in relation to sex steroids and water temperature - Pamela Sabrina del Fresno; Darío César Colautti; Gustavo Emilio Berasain; Leandro Andrés Miranda (New Zealand Journal of Marine and Freshwater Research, 2022)
The relationship between water temperature and gonadal maturation of a landlocked ecophenotype of marine pejerrey ( Odontesthes argentinensis ) in La Salada de Pedro Luro lake was analysed during three spawning seasons. Mainly vitellogenic females were found in August (winter), some ovulating in October (mid‐spring) and with atretic oocytes in December (end of spring). In accordance with this, gonadosomatic index (GSI) and estradiol plasma levels showed maximum values in October (7.6 ± 0.7%; 1631.7 ± 256.1 pg/mL) and minimum values in December (1.2 ± 0.3%; 230,33 ± 8,74 pg/mL). Spermiating males were found during the whole spawning season and only arrested in December. The highest GSI values were recorded in October (4.6 ± 0.2%) and for testosterone (T) in August (1113.2 ± 503.8 pg/mL). Meanwhile, in December the minimum GSI and T plasma values (1.3 ± 0.6%, 323.8 ± 5.3 pg/mL) were observed. According to the Fourier fitted models, temperature explains more than 70% of the observed variation in GSI in both sexes. Moreover, the total GSI variation range was positively related to the total temperature range variation experienced during the reproductive seasons demonstrating the influence of this environmental variable on maturation intensity and dynamics.